Are there long-term earnings scars from youth unemployment in Germany? - Joachim Möller; Matthias Umkehrer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We analyze the relationship between early-career unemployment and prime-age earnings with German administrative linked employer-employee data. The careers of more than 720,000 male apprenticeship graduates from the cohorts of 1978 to 1980 are followed over 24 years. On average, early-career unemployment has substantial negative effects on earnings accumulated later in life. An identification strategy based on plant closure of the training firm at the time of graduation suggests that the revealed correlation is not the result of unobserved heterogeneity. Scarring effects also vary considerably across the earnings distribution. Workers with a high earnings potential are able to offset adverse consequences of early-career unemployment to a large extent. Workers who are located at the bottom of the prime-age earnings distribution, in contrast, suffer substantial and persistent losses. Our findings imply that a policy with the aim of preventing early-career unemployment would have long-lasting beneficial effects on future earnings.
urn:nbn:de:bsz:180-madoc-373204
Keywords: J30; J69; C21; C26; 330; scarring; state dependence; youth unemployment